Shoulder injury patterns and trends in the national football league: an epidemiological analysis - Fares, M. Y.; Daher, M.; Boufadel, P.; Singh, J.; Bdeir, A.; Koa, J.; Lopez, J.; Goltz, D.; Abboud, J. A. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Athletic movements in American football render the shoulder vulnerable to injury. The aim of this study was to explore the epidemiology of shoulder injuries in the National Football League (NFL). METHODS: Injury data from the 2019-2022 seasons were extracted from official NFL website and secondary resources. Injury parameters included type, severity, week, position and other demographic characteristics. Injury rates were calculated per 1000 athletic exposures (AE) and statistical analyses were used to determine whether any significant differences exist in injury patterns across different positions and types. RESULTS: A total of 6732 injuries were reported during our study period, of which 452(6.7%) were attributed to the shoulder, leading to an injury rate of 4.5 per1000 AE. Linebackers, cornerbacks, wide receivers, and safety positions had significantly higher numbers of shoulder injuries than other defensive and offensive positions. Most injuries were mild (66%, P<0.001). Muscular (40.9%) and ligamentous (37.4%) injuries were the most common injury types. Fractures and ligamentous injuries were significantly more severe than muscular and other injuries (P<0.05). Even though week 17 had the highest mean number of shoulder injuries at 10.75/season, there was no apparent shoulder injury distribution trend across the football season. CONCLUSIONS: Shoulder injuries are common in American football. Introducing a deidentified injury registry that provides detailed injury information in the NFL may help develop better prevention strategies and protocols.